Acute myocardial infarction caused by paradoxical embolism with concomitant pulmonary embolism. (21st July 2011) - Hline, Aye; Malik, Nikesh; Khokhar, Azhar; Aggarwal, Rajesh
Abstract : An 86-year-old lady presented with an acute inferior ST elevation myocardial infarction. The coronary angiogram showed a thrombotic occlusion of the right coronary artery, which was aspirated, but there was no underlying lesion to stent. The patient remained very hypoxic on the ward with clear lung fields and was found to also have multiple pulmonary emboli on CT pulmonary angiogram. Paradoxical embolism was suspected as the cause of myocardial infarction and subsequent echocardiography studies indeed confirmed the presence of a patent foramen ovale. Although rare, this mechanism should be considered in patients presenting with acute coronary syndromes without significant underlying coronary artery disease.